A computational and experimental approach to studying NFkB signaling in response to single, dual, and triple TLR signaling - Thalia Newman; Annarose Taylor; Sakhi Naik; Swati Pandey; Kimberly Manalang; Robert A. Kurt; Chun Wai Liew (ImmunoInformatics)
Modeling and experimental data were used to evaluate how monocytes would respond to dual TLR4/TLR5 and dual TLR4/TLR7 signaling analogous to how the cells would respond to simultaneously encountering different types of pathogens. Both TLR4/TLR5 and TLR4/TLR7 signaling resulted in a decreased NFkB response relative to signaling through a single TLR. The NFkB response also decreased when all three signaling cascades were triggered. The model suggested that competition between the signaling pathways led to the impaired response when the cells were exposed to multiple TLR agonists, however adjusting the level of IRAKs and TABs in the model was insufficient to overcome competition between the signaling pathways. To experimentally examine how modifying TLR signaling proteins would impact the NFkB response to multiple TLR agonists, cells were pre-conditioned with lipopolysaccharide and the response to single, dual, and triple TLR signaling was followed. Pre-conditioning led to a reduction in the NFkB response to all three agonists, likely a consequence of decreased tlr4, tlr5, tlr7, nfkb, tab1, tab2, and tab3 expression. Collectively, the model supported exploration of the effects of multiple agonists on the signaling pathways and the effectiveness of adjusting the level of TLR signaling proteins in improving the NFkB response. These experiments and data show the importance of having a model capable of integrating multiple TLR signaling cascades since data generated by the model of a single TLR signaling cascade could not predict how the cells would respond when multiple TLR signaling cascades were activated.